Zapis scenariuszowy w emigracyjnej trylogii Miodraga Bulatovicia - Szukalska, Aldona (Slavia Occidentalis, 2011)
The article entitled “Script Notation in the Emigrational Trilogy of Miodrag Bulatović” is devoted to issues connected with motion pictures, and especially to a quite rarely encountered form, the script notation present in the prose of the Serbian writer of the Montenegro origin. The use of the qualities typical of the film is connected with abandoning the elements characteristic for literature, such as psychologization of the protagonists, the ideas and intellectualism, and replacing them by enhancing visual effects, introducing behavioural techniques or the moving camera eye, recording, in a documentary manner, the behaviour of characters as well as the space, and also limiting narration and the domination of description. The article concentrates mostly on the last novels of the Serbian author, which testify not only the changes occurring in the sphere of the visualization technique but also the transition from existential to moral problems.